2011
DOI: 10.1038/cr.2011.76
|View full text |Cite
|
Sign up to set email alerts
|

Indian hedgehog mutations causing brachydactyly type A1 impair Hedgehog signal transduction at multiple levels

Abstract: Brachydactyly type A1 (BDA1), the first recorded Mendelian autosomal dominant disorder in humans, is characterized by a shortening or absence of the middle phalanges. Heterozygous missense mutations in the Indian Hedgehog (IHH) gene have been identified as a cause of BDA1; however, the biochemical consequences of these mutations are unclear. In this paper, we analyzed three BDA1 mutations (E95K, D100E, and E131K) in the N-terminal fragment of Indian Hedgehog (IhhN). Structural analysis showed that the E95K mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
3

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 55 publications
(105 reference statements)
2
45
0
3
Order By: Relevance
“…IHH is synthesized as a 45 kDa precursor but is subsequently cleaved to an active 19 kDa Nterminal fragment that undergoes palmitoylation, which is required for multimerization and leads to about a 30-fold increase in bioactivity [33]. This N-terminal fragment is also modified by attachment of cholesterol, and cholesterol interactions with heparan sulfate proteoglycans facilitate longrange diffusion [34]. Cholesterol addition is also required for targeting to membrane lipid rafts and multimerization.…”
Section: Discussionmentioning
confidence: 97%
“…IHH is synthesized as a 45 kDa precursor but is subsequently cleaved to an active 19 kDa Nterminal fragment that undergoes palmitoylation, which is required for multimerization and leads to about a 30-fold increase in bioactivity [33]. This N-terminal fragment is also modified by attachment of cholesterol, and cholesterol interactions with heparan sulfate proteoglycans facilitate longrange diffusion [34]. Cholesterol addition is also required for targeting to membrane lipid rafts and multimerization.…”
Section: Discussionmentioning
confidence: 97%
“…Indian HH is a pro-osteogenic factor that positively regulates intramembranous calvarial ossification by modulating BMP signaling [Lenton et al, 2011]. Interestingly, in a pattern analogous of BMP2 and BMP14 [Plöger et al, 2008], heterozygous missense mutations in Indian HH also result in brachydactyly [Ma et al, 2011]. …”
Section: Genetic Etiopathogenesis Of Craniosynostosismentioning
confidence: 99%
“…Indian hedgehog (IHH) was the first identified gene to be associated with BDA1 [7].The IHH gene, which encodes a member of the Hedgehog family of signaling proteins, is known for its role in endochondral ossification: regulate the balance between growth and ossification of the developing bones [5]. The IHH protein operates through a feedback control mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the X-ray crystal structure of SHH, McLellan, et al showed that these residues are located within a calcium binding site, an important domain for mediating interactions with PTCH1, HIP1, CDO and GAS1 [17]. In particular, p.D100E had been shown to affect IHH interaction with PTCH1 and HIP1, reducing its capacity to induce cellular differentiation [16], whereas p.D100E was shown to change the Hh local tertiary structure and intracellular fate [5] [3,[20][21]. Not all DBA1 individuals with these pathogenic variants exhibited short stature, but they were shorter than non-carrier family members [3,[19][20][21], suggesting variants at this mutational hotspot can affect the growth to various degree but with reduced penetrance for short stature.…”
Section: Discussionmentioning
confidence: 99%